Internalization and distribution of three alpha1-adrenoceptor subtypes in HEK293A cells before and after agonist stimulation - Wang Shu-yi; Song Yao; Xu Ming; He Qi-hua; Han Qi-de; Zhang You-yi (Acta Pharmacologica Sinica, 2016)
Aim: To examine the subcellular distribution of the 3 α1-adrenoceptor (α1-AR) subtypes and their internalization and trafficking upon agonist stimulation in human embryonic kidney 293A cells. Methods: Confocal real-time imaging, enzyme linked immunosorbent assay (ELISA) and whole cell [3H]-prazosin binding assay were applied to detect the distribution and localization of the 3 α1-AR subtypes. Results: α1A-AR was found both on the cell surface and in the cytoplasm; α1B-AR, however, was predominantly detected on the cell surface, while α1D-AR was detected mainly in the intracellular compartments. After stimulation with phenylephrine, localization changes were detected by confocal microscopy for α1A- and α1B-AR, but the localization of α1D-AR were unaffected. Phenylephrine stimulation promoted a more rapid internalization of α1B-AR than α1A-AR. α1D-AR internalization was detected only by ELISA. Whole cell [3H]-prazosin binding assay showed that α1A-AR functional receptors were detected both on the cell surface and in the cytoplasm; α1B-AR, however, were detected predominantly on the cell surface, while α1D-AR were detected mainly in intracellular compartments. Phenylephrine stimulation promoted internalization of α1A- and α1B-AR. Conclusion: Phenylephrine stimulation induced changes in the localization of the 3 α1-AR.